Tourists’ Shopping Expectation, Perceived Value and Shopping Satisfaction in Malaysia / Anis Liyana Buliah ... [et al.] - Buliah, Anis Liyana; Azmi, Azila; Aminudin, Norliza; Abdullah, Dahlan; Mohd Asri, Dian Aszyanti Atirah (Universiti Teknologi MARA Cawangan Selangor and UiTM Press, 2018)
The tourism industry is one of the most important industries to help a country in improving its economy. With the arrival of every foreign tourist, a country’s total receipts will simultaneously increase due to a tourist’s needs and want which are translated through the spreading of various economic activities. Among favorite economic activities during vacation is shopping. This study will explore the relationship between shopping expectation and perceived value, the relationship between shopping expectation, perceived value and disconfirmation, the relationship between perceived value, disconfirmation and shopping satisfaction and, the relationship between disconfirmation and shopping satisfaction. The Expectation-Confirmation Theory (ECT) involves three main antecedents which are the expectation, disconfirmation and perceived performance. For this study, ECT was used to formulate a proposed model for this study which will enhance Malaysia’s position as a shopping hub.